Practical nutritional recovery strategies for elite soccer players when limited time separates repeated matches - Mayur Krachna Ranchordas; Joel T. Dawson; Mark Russell (Taylor & Francis Group, 2017)
Specific guidelines that aim to facilitate the recovery of soccer players from the demands of training and a congested fixture schedule are lacking; especially in relation to evidence-based nutritional recommendations. The importance of repeated high level performance and injury avoidance while addressing the challenges of fixture scheduling, travel to away venues, and training commitments requires a strategic and practically feasible method of implementing specific nutritional strategies. Here we present evidence-based guidelines regarding nutritional recovery strategies within the context of soccer. An emphasis is placed on providing practically applicable guidelines for facilitation of recovery when multiple matches are played within a short period of time (i.e. 48 h). Following match-play, the restoration of liver and muscle glycogen stores (via consumption of ~1.2 g⋅kg−1⋅h−1 of carbohydrate) and augmentation of protein synthesis (via ~40 g of protein) should be prioritised in the first 20 min of recovery. Daily intakes of 6-10 g⋅kg−1 body mass of carbohydrate are recommended when limited time separates repeated matches while daily protein intakes of >1.5 g⋅kg−1 body mass should be targeted; possibly in the form of multiple smaller feedings (e.g., 6 × 20-40 g). At least 150% of the body mass lost during exercise should be consumed within 1 h and electrolytes added such that fluid losses are ameliorated. Strategic use of protein, leucine, creatine, polyphenols and omega-3 supplements could also offer practical means of enhancing post-match recovery.